Synthesis of 1,2,3-triazoles using Grignard reactions through the protection of azides - Namioka, Rina; Suzuki, Minori; Yoshida, Suguru (Frontiers in Chemistry, 2023)
An efficient method to prepare organomagnesium intermediates having a protected azido group is disclosed. Protection of azido groups with di(tert-butyl)(4-(dimethylamino)phenylphosphine (Amphos) and following iodine-magnesium exchange realized the preparation of organomagnesium intermediates, which served in the synthesis of diverse azides by transformations with various electrophiles followed by deprotection with elemental sulfur. Further, click reactions of azides with alkynes enabled us to synthesize a wide variety of 1,2,3-triazoles.